Stress, symptoms and opinions on menopause in relation to depressed mood in women aged 45-55 years. An analysis within the framework of modified psychosocial model of menopausal depression - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2006)
Objective: The aim of the study was to look for factors linked to menopausal depression. The study was based on the modified version of psychosocial model of menopausal depression developed by J.G. Greene. It was hypothesized that depression would be lined to level of stress, attitudes towards menopause and intensity of symptoms. Factors affecting the level of stress, such as social support, were also considered. Material and methods: The participants were 183 women aged 45-55 yrs with no diagnosis of clinical depression. The measures included Beck Depression Inventory, Menopause Representation Questionnaire, Social Support Scale, Social Readjustment Rating Scale, Scale of Stress. Multiple regression analysis, Pearson correlation coefficients and t-tests were used. Results: The findings indicate that the level of depression was explained in 38% by the high level of experienced stress and high intensity of menopausal symptoms. It was also found that negative opinions on menopause were not linked to depression. The opinions that were more important for depression were positive ones, particularly the opinion of menopausal transition being the new phase of a female life. Sharing this opinion were linked to lower level of depression. Together with symptoms and stress this variable explained 45% of the variance of depression. Conclusion: The menopausal depression is increased by the intensity of symptoms and the high level of experienced and decreased by the opinion that menopausal transition is the new phase of a female life.